Accelerated schools programmes: Assessing their effectiveness - Gaziel, Haim (International review of education, 2001)
Accelerated School Programmes (ASPs) apply three principles designed to raise schools' effectiveness and to narrow the gap between low-achieving and high achieving students. These principles are: (1) giving the school a unifying purpose or vision; (2) allowing the school greater autonomy in its own managment; (3) developing a collaborative approach to teaching, involving teachers, students, parents and the community. This article examines the effectiveness of ASPs on the basis of a study of four comprehensive schools in Israel. While the size of the sample is small, the positive results indicate that similar research on a wider scale would be valuable in shaping future educational policy. (DIPF/orig.)